Effect of a Poly Herbal Ingredient on Day Old Chick Quality by Feeding in Parent Flocks - Manoharan, S.; Ramesh, S.; Parthiban, M.; Koteeswaran, A.; Chandran, N.D.J.; Reddy, M. Ranga (International Journal of Poultry Science, 2004)
A trial was undertaken in 99 numbers of white leghorn layer parent stock to study the indirect effect of stresroak (a poly herbal feed additive) on overall chick quality improvement, seven day mortality and maternal antibody transfer to chicks. The stresroak feed mix was given @ 2kg per ton of feed and water supplement @ 20ml / day for 100 birds for one month period. The chicks were received two weeks after supplementation at weekly interval for 5 weeks period to assess the chick quality. The results showed that the chick quality scores of the stresroak supplemented groups were highly significantly different from control group (P<0.01). The first week mortality recorded for the three treatment groups revealed a highly significant difference (P<0.01) upon comparison with control group. The maternal antibody against Ranikhet disease in the stresroak supplemented groups showed a highly significant difference (P<0.01) in the transfer of maternal antibody when compared to control group.